Arabidopsis GEX1 Is a Nuclear Membrane Protein of Gametes Required for Nuclear Fusion During Reproduction - Nishikawa, Shuh-ichi; Yamaguchi, Yuki; Suzuki, Chiharu; Yabe, Ayaka; Sato, Yuzuru; Kurihara, Daisuke; Sato, Yoshikatsu; Susaki, Daichi; Higashiyama, Tetsuya; Maruyama, Daisuke (Frontiers in Plant Science, 2020)
During the life cycle of flowering plants, nuclear fusion, or karyogamy, occurs three times: once during female gametogenesis, when the two polar nuclei fuse in the central cell, and twice during double fertilization. In Arabidopsis thaliana, nuclear fusion events during sexual reproduction proceed without the breakdown of the nuclear envelope, indicating that nuclear membrane fusion is essential for the completion of this process. Arabidopsis gamete expressed 1 (GEX1) is a membrane protein that is conserved among plant species. GEX1 shares homology with the yeast karyogamy protein Kar5, which is primarily expressed in the nuclear membrane. The GEX1 family represents a putative karyogamy factor. Herein, we show that GEX1 is required for the nuclear fusion events in Arabidopsis reproduction. GEX1-deficient mature female gametophytes were found to contain two unfused polar nuclei in close proximity within the central cell. Electron microscopy showed that the outer membrane of the polar nuclei was connected via the endoplasmic reticulum, whereas the inner membrane remained unfused. These results indicate that GEX1 is involved in polar nuclear membrane fusion following the fusion of the outer nuclear membrane. Furthermore, sperm nuclear fusion events were defective in the fertilized egg and central cell following the fertilization of gex1-1 female gametophytes by gex1-1 pollen. An analysis of GEX1 localization in the female gametophyte using a transgenic line expressing GFP-tagged GEX1 driven by the GEX1 promoter showed that GEX1 is a nuclear membrane protein in the egg and central cell. Time-lapse live-cell imaging showed that in developing female gametophytes, the nuclear GFP-GEX1 signal was first detectable in the central cell shortly before the polar nuclei came in close contact, and then in the egg cell. Thus, we suggest that the GEX1-family proteins are nuclear membrane proteins involved in karyogamy in the reproduction of eukaryotes including flowering plants.